2020
DOI: 10.3389/fpsyt.2020.555836
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Connectivity of Thalamo-Cortical Networks in First-Episode, Treatment-Naive Somatization Disorder

Abstract: Background Dysfunctions of the thalamus and its projections to cortical cortices have been implicated in patient with somatization disorder (SD). However, changes in the anatomical specificity of thalamo-cortical functional connectivity (FC) in SD remain unclear. Methods Resting-state fMRI scans were collected in 25 first-episode, drug-naive patients with SD, as well as 28 sex-, age-, and education-matched healthy controls. We parcellated the thalamus with seven predefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…This is in general agreement with our findings of a widespread network of white matter pathways related to somatization in boys with SOR, including cortico-cortical association tracts, cortico-subcortical projection tracts, and cerebellar pathways. Alterations of corticothalamic functional connectivity to somatosensory, auditory, and visual cortex have also been found in somatization disorder in adults using resting state functional MRI (fMRI) [ 63 ], which thereby implicates the PLIC and other posterior sensory WM tracts.…”
Section: Discussionmentioning
confidence: 99%
“…This is in general agreement with our findings of a widespread network of white matter pathways related to somatization in boys with SOR, including cortico-cortical association tracts, cortico-subcortical projection tracts, and cerebellar pathways. Alterations of corticothalamic functional connectivity to somatosensory, auditory, and visual cortex have also been found in somatization disorder in adults using resting state functional MRI (fMRI) [ 63 ], which thereby implicates the PLIC and other posterior sensory WM tracts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pan et al (2019) found that patients with SSD exhibited an increased global functional connectivity (GFC) in the right inferior temporal gyrus and left superior occipital gyrus and a decreased GFC in the right insula compared with healthy controls (HCs). In contrast, Zhao et al (2020) demonstrated an enhanced thalamocortical functional connectivity (FC) in first-episode, drug-naive patients with SSD. In terms of structural abnormalities, Yildirim et al (2012) found significantly smaller pituitary volumes in somatization patients compared with HCs.…”
Section: Introductionmentioning
confidence: 99%